Obstructive Sleep Apnea in Patients With Primary-open Angle Glaucoma: No Role for a Screening Program. Issue 8 (August 2019) - Wozniak, Dariusz; Bourne, Rupert; Peretz, Gil; Kean, Jane; Willshire, Catherine; Harun, Shabbir; Villar, Sofia; Chiu, Yi-Da; Smith, Ian
Abstract : Précis: In this study, we found a high prevalence of obstructive sleep apnea (OSA) among patients with primary open-angle glaucoma (POAG) but this was not different (nor was OSA more severe) to matched people without glaucoma. Rationale: It has been proposed that OSA might be a contributing factor in the development of POAG and by extension that there could be a role for screening people with POAG for OSA. Objectives: To assess whether the prevalence of OSA among patients with POAG is different from that in people without glaucoma and to examine for associations between apnea-hypopnea index (AHI) and markers of functional and structural changes in POAG. Methods: Unselected POAG patients and control subjects were consecutively recruited in a single center. A comprehensive ocular assessment and nocturnal multichannel cardiorespiratory monitoring were performed. Results: Data from 395 participants, 235 POAG patients, and 160 controls were analyzed. The prevalence of OSA was 58% [95% confidence interval (CI), 52-65] in POAG patients and 54% (95% CI, 47-62) in controls, with 22% (95% CI, 16-27) of POAG patients and 16% (95% CI, 11-22) of controls diagnosed with moderate or severe OSA. A total of 160 POAG participants were matched to the controls using propensity score matching. There was no significant difference in OSA prevalence between the matched groups ( P =0.91 for AHI≥5 and P =0.66 for AHI≥15). The AHI was not associated with the severity of visual field defect or retinal nerve fiber layer thinning after adjustment for confounders. Conclusions: This study confirms a high prevalence of OSA among patients with POAG which is, however, not higher than in people without glaucoma matched for known OSA risk factors. Our results do not support screening for OSA in patients with POAG. Abstract : Supplemental Digital Content is available in the text.